miR-340-5p Suppresses Aggressiveness in Glioblastoma Multiforme by Targeting Bcl-w and Sox2 - Sanghwa Kim; Jae Yeon Choi; Hyun Jeong Seok; Myung-Jin Park; Hee Yong Chung; In Hwa Bae (Elsevier, 2019)
Glioblastoma multiforme (GBM), a particularly aggressive type of malignant brain tumor, has a high mortality rate. Bcl-w, an oncogene, is reported to enhance cell survival, proliferation, epithelial-mesenchymal transition (EMT), migratory and invasive abilities, and stemness maintenance in a variety of cancer cell types, including GBM. In this study, we confirmed that Bcl-w-induced conditional medium (CM) enhances tumorigenic phenotypes of migration, invasiveness, and stemness maintenance. Notably, platelet-derived growth factor-A (PDGF-A) expression, among other factors of the tumor environment, was increased by CM of Bcl-w-overexpressing cells, prompting investigation of the potential correlation between Bcl-w and PDGF-A and their effects on GBM malignancy. Bcl-w and PDGF-A levels were positively regulated and increased tumorigenicity by Sox2 activation in GBM cells. miR-340-5p was further identified as a direct inhibitor of Bcl-w and Sox2. Overexpression of miR-340-5p reduced mesenchymal traits, cell migration, invasion, and stemness in GBM through attenuating Bcl-w and Sox2 expression. Our novel findings highlight the potential utility of miR-340-5p as a therapeutic agent for glioblastoma multiforme through inhibitory effects on Bcl-w-induced PDGF-A and Sox2 activation. Keywords: GBM, tumor microenvironment, Bcl-w, PDGF, miR-340-5p, Sox2